2017
DOI: 10.1038/nrgastro.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Advances in image enhancement in colonoscopy for detection of adenomas

Abstract: High-quality colonoscopy is mandatory to prevent adenoma recurrence and colorectal cancer. In the past few years, technical advances have been developed with the purpose of improving adenoma detection rate (ADR), one of the most important validated colonoscopy quality benchmarks. Several techniques or devices are used to optimize visualization: observation techniques; add-on devices; auxiliary imaging devices; colonoscopes with increased field of view; and colonoscopes with an integrated inflatable reusable ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 102 publications
1
32
1
1
Order By: Relevance
“…GASTROINTESTINAL CANCERS REMAIN the commonest cancers worldwide . Recent development in image‐enhanced endoscopy (IEE) as well as the increased implementation of gastrointestinal cancer screening programs for colorectal and gastric cancers has led to earlier diagnosis of gastrointestinal cancers . With improvement in endoscopic recognition of early gastrointestinal cancers, as well as implementation of gastrointestinal cancer screening programs worldwide, there is an increasing trend in recognition of early gastric, esophageal and colon neoplasia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GASTROINTESTINAL CANCERS REMAIN the commonest cancers worldwide . Recent development in image‐enhanced endoscopy (IEE) as well as the increased implementation of gastrointestinal cancer screening programs for colorectal and gastric cancers has led to earlier diagnosis of gastrointestinal cancers . With improvement in endoscopic recognition of early gastrointestinal cancers, as well as implementation of gastrointestinal cancer screening programs worldwide, there is an increasing trend in recognition of early gastric, esophageal and colon neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent development in image-enhanced endoscopy (IEE) as well as the increased implementation of gastrointestinal cancer screening programs for colorectal and gastric cancers has led to earlier diagnosis of gastrointestinal cancers. 2,3 With improvement in endoscopic recognition of early gastrointestinal cancers, as well as implementation of gastrointestinal cancer screening programs worldwide, there is an increasing trend in recognition of early gastric, esophageal and colon neoplasia. Endoscopic submucosal dissection (ESD) has been developed to achieve en bloc resection for upper gastrointestinal neoplasia, 4,5 whereas colorectal ESD is increasingly carried out for treatment of laterally spreading tumors detected during screening colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In these core sessions, it was shown that several convenient and less invasive colonoscopic modalities have been developed in recent years. IEE improves the detectability of colorectal lesions, and predicts precise histopathological diagnosis using magnification . However, at present, there remain some problems.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Novel methods were therefore developed to overpass anatomical difficulties of the colon, enable more accurate, even microscopic identification of abnormalities in the size, density and shape of crypts and vessels [13,[16][17][18]. They can be roughly divided into three categories, ones that improve overall mucosal examination and increase the polyp detection, those that enable more thorough examination (almost histological) of the detected lesions and minimally invasive techniques.…”
Section: Introductionmentioning
confidence: 99%